Psychological Distress, Early Behavioral Response, and Perception Toward the COVID-19 Pandemic Among Health Care Workers in North Shoa Zone, Oromiya Region - Jemal, Kemal; Deriba, Berhanu Senbeta; Geleta, Tinsae Abeya (Frontiers in Psychiatry, 2021)
Abstract Background: The coronavirus disease 2019 (COVID-19) pandemic has a significant psychological impact on health care workers (HCWs). Therefore, this study inspects mental health status, behavioral response, and perception among HCWs (nurses, physicians, and medical laboratory workers) during the COVID-19 pandemic in public health care facilities. Methods: A facilities-based cross-sectional study was conducted in July 2020. A simple random sampling technique was used to select study participants. Data were collected by self-report administered questionnaire using Patient Health Questionnaire-9 (PHQ-9) for depression, General Anxiety Disorder-7 (GAD-7) for anxiety, Insomnia Severity Index (ISI) for insomnia, Impact of Event Scale-Revised (IES-R) for psychological distress, Perceived Threat Scale for perception, and Behavioral Response Inquiry for the behavioral response. Moreover, bivariable and multivariable logistic regressions analysis was used to identify the association between dependent and independent variables at p-value <0.05. Results: A total of 417 (98.6%) HCWs responded to a self-administered questionnaire. The proportion of HCWs who had moderate to severe symptoms of psychological distress, depression, anxiety, and insomnia during the COVID-19 pandemic were 58%, 16.3%, 30.7%, 15.9%, respectively. Three-fifth of the nurses, medical laboratory professionals (62.2%), and physicians (59.2%) had reported good behavioral responses towards the COVID-19 pandemic. More than three-fifths of the nurses had reported poor perception toward the COVID-19 pandemic. Conversely, 61.2% of physicians and three-fourth (75.5%) of medical laboratory professionals had reported good perception toward the COVID-19 pandemic. Female and married participants, working in the emergency unit, having poor behavioral responses, and poor perception towards the COVID-19 pandemic were significantly associated with symptoms of psychological distress, depression, anxiety, and insomnia. Conclusions: Psychological impacts among physicians, nurses, and medical laboratory professionals are high during the COVID-19 pandemic. Ethiopian Federal Ministry of Health should be protected all HCWs' psychological well-being during the COVID-19 pandemic with appropriate interventions and accurate information response.